Quality culture and its role in service delivery at a university of technology - Mdena, Funeka (Cape Peninsula University of Technology, 2019)
Customer satisfaction is a topic of global interest in higher education and it also forms the backdrop of the research presented in this thesis. This study focuses on the employees (academics and non-academics) in the Faculty of Education at a South African university of technology (UoT) who play a key role in providing the services that their customers receive. The study is underpinned by the understanding that in order for the customer’s experience of service provision to be positive, a healthy relationship between the customer and the service provider is critical. The organization, in this case a higher education institution, has to have a sense of quality culture in order for the service provider to maintain a good relationship with a customer. Quality culture assessment can help to better understand complex organizational culture and its impact on service delivery. Quality culture assessment also helps to direct the implementation of organizational changes for better service delivery structures. The type of quality culture dominant in an organization may positively or negatively affect service quality, employee performance and motivation. As a result, the service delivery experience of the customer may be influenced. Quality culture affects the way in which employees interact with each other and with their customers. This study therefore, presents an inquiry into quality culture within a higher education context with the aim to evaluate quality culture within the Faculty of Education at a UoT using quality management principles (QMPs) as a framework. This study employed QMPs because of their increased effectiveness in enhancing customer satisfaction and improving customer loyalty. The quality management principles are: customer focus, leadership, engagement of people, process approach, improvements, evidence-based decisions and relationship management (ISO 9001, 2015:Online). This study used a quantitative research approach and was designed as a survey case study. Data was collected through a structured questionnaire that was disseminated to all the academic and non-academic staff in the Faculty of Education at the UoT. Statistical Package for Social Sciences (SPSS) software was used as a tool for data analysis. Findings in this study reveal that a safe working environment, communication between employees, communication between management and employees, in addition to good working relationships, may affect service quality in the Faculty of Education at the UoT. This implies that having a healthy working environment in an organization is beneficial for employees in order to perform their duties better and to provide quality services to their customers. In an organization with good quality culture, there is close cooperation between employees which leads to good service quality. If the institution under study is concerned with providing value to customers, it needs to consider improving customer value by formally applying QMPs throughout the organization. QMPs are central to the practice of quality management and service delivery. The findings of this study suggest that quality culture affects service quality in the Faculty of Education at the UoT as some of the quality management principles are lacking. This study recommends that the Faculty of Education have a closer look at improving communication between employees, communication between management and employees, in addition to encouraging good working relationships as well as an enabling environment that allows employees to work efficiently. It is also recommended that quality culture be on the Faculty of Education’s agenda in order to enhance the service delivery experience of customers. The Faculty of Education should support a quality culture environment by providing appropriate structures such as service delivery structures within their organizations. These structures may be needed in order to facilitate, maintain and show commitment of staff members towards a quality culture environment and service delivery. Furthermore, these structures may contribute to quality culture by introducing new shared values and behavioural norms that might facilitate the long-term success and well-being of the organization. It is also recommended that the institution under study formally apply quality management principles throughout the organization for the purpose of improving customer value, customer experience and meeting customer needs.
Thesis (MTech (Quality))--Cape Peninsula University of Technology, 2019.
Keywords: Universities and colleges -- South Africa -- Western Cape -- Administration; Quality assurance -- South Africa -- Western Cape; Education, Higher -- South Africa -- Western Cape -- Standards; Organizational culture -- South Africa -- Western Cape